Optimal Parallel Construction of Minimal Suffix and Factor Automata - Breslauer, Dany; Hariharan, Ramesh (BRICS Report Series, 1995)
This paper gives optimal parallel algorithms for the construction of the smallest deterministic finite automata recognizing all the suffixes and the factors of a string. The algorithms use recently discovered optimal parallel suffix tree construction algorithms together with data structures for the efficient manipulation of trees, exploiting the well known relation between suffix and factor automata and suffix trees.